Determinants of Low Birth Weight in Cilacap District (Journal of Maternal and Child Health, 2020)
Background: Low birth weight (LBW) is closely related to the increased risk of child morbidity and mortality, disruption of developmental growth and in the long-run has an increased risk of chronic disease in their adulthood. This study aims to analyze the effect of nutritional status at the beginning of pregnancy, maternal education and family expenditure on the incidence of low birth weight (LBW) in Cilacap District.Subjects and Method: This study is an obser